PENGARUH CAPITAL INTENSITY, FIXED ASSET INTENSITY DAN DEFERRED TAX EXPENSE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR INDUSTRY CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Silviny Wijaya; Latersia Br Gurusinga; Yusnaini Yusnaini (LPPM Universitas Putera Batam, 2026)
This study aims to determine and analyze the influence of capital intensity, fixed asset intensity and deferred tax expense on tax avoidance in companies in the non-cyclical consumer industry sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. This research is quantitative research using secondary data obtained from the financial statements of companies in the non-cyclicals consumer industry sector on the Indonesia Stock Exchange The population used in this study is all companies in the non-cyclicals consumer industry sector listed on the IDX for the 2021-2024 period as many as 132 companies. The sampling technique in this study uses purposive sampling with several criteria determined so that a total of 35 companies with a total of 140 observation data was obtained. The data analysis techniques used were descriptive statistics, panel data regression selection, classical assumption test and hypothesis testing using the E-Views version 13 program. The results of the study show that the variables free of capital intensity, fixed asset intensity and deferred tax expense have a positive and significant effect on tax avoidance. Simultaneously, the variables free of capital intensity, fixed asset intensity and deferred tax expense have a significant effect on tax avoidance.